Resolvin E1 attenuates atherosclerosis in absence of cholesterol-lowering effects and on top of atorvastatin. (July 2016) - Salic, Kanita; Morrison, Martine C.; Verschuren, Lars; Wielinga, Peter Y.; Wu, Lijun; Kleemann, Robert; Gjorstrup, Per; Kooistra, Teake
Abstract: Background and aims: Besides LDL-cholesterol, local vascular inflammation plays a key role in atherogenesis. Efficient therapies to treat the inflammatory component of the disease have not been established. The discovery of specialized inflammation-resolving mediators, such as resolvins may provide new opportunities for treatment. This study examines whether the ω-3 fatty acid eicosapentaenoic acid-derived resolvin E1 (RvE1), can reduce atherosclerosis, when administered alone or in combination with a cholesterol-lowering statin. Methods: ApoE*3Leiden mice were fed a hypercholesterolemic diet for 9 weeks and subsequently treated with RvE1-low (1 mg/kg/day), RvE1-high (5 mg/kg/day), atorvastatin (1.5 mg/kg/day) or the combination of atorvastatin and RvE1-low for the following 16 weeks. Results: RvE1-low and RvE1-high reduced atherosclerotic lesion size to the same extent (−35%; p < 0.05), attenuated the formation of severe lesions, also seen as a proportional increase in the presence of mild lesions, but did not alter plasma cholesterol levels. Cholesterol-lowering atorvastatin reduced atherosclerosis (−27%, p < 0.05), and the combination of RvE1 and atorvastatin further attenuated lesion size (−51%, p < 0.01) and increased the content of mild lesions. RvE1 did not affect plasma SAA, E-selectin, VCAM-1 or MCP-1 but did reduce plasma EPHX4 and down-regulated the local expression of pro-atherogenic genes in the aortae, (e.g. Cd74, Cd44, Ccl2, Ccr5 and Adam17 ) and significantly inactivated IFN-γ ( p < 0.001) and TNF-α ( p < 0.001) signalling pathways. Conclusions: RvE1 attenuates atherogenesis both alone and on top of a statin. The local effects of RvE1 are demonstrated by the modulated aortic expression of genes involved in inflammatory and immune responses, without altering plasma cholesterol or circulating SAA. Highlights: Resolvin E1 attenuates atherogenesis both alone and on top of a statin. Resolvin E1 attenuates atherosclerosis without affecting plasma lipids. Resolvin E1 improves lesion severity. Resolvin E1 has local anti-inflammatory effects within the aorta.